Do rice prices follow a random walk? Evidence from Markov switching unit root tests for Asian markets. (24th August 2016) - Valera, Harold Glenn A.; Lee, Jim
Abstract: This study revisits the issue of mean reversion in the import rice prices of six Asian countries over the period between 1995 and 2015. Augmented Dickey Fuller tests with a conventional linear regression model support the presence of a unit root in the levels of the price data. However, when regressions allow for Markov switching in coefficients and variances to capture periodic shifts in levels and volatilities, there is strong evidence against the unit‐root null hypothesis in favor of stationarity over much of the observation period.